2007
DOI: 10.1101/gr.5826307
|View full text |Cite
|
Sign up to set email alerts
|

The evolutionary history of human DNA transposons: Evidence for intense activity in the primate lineage

Abstract: Class 2, or DNA transposons, make up ∼3% of the human genome, yet the evolutionary history of these elements has been largely overlooked and remains poorly understood. Here we carried out the first comprehensive analysis of the activity of human DNA transposons over the course of primate evolution using three independent computational methods. First, we conducted an exhaustive search for human DNA transposons nested within L1 and Alu elements known to be primate specific. Second, we assessed the presence/absen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
269
1
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 276 publications
(282 citation statements)
references
References 59 publications
7
269
1
5
Order By: Relevance
“…Initially in human, the CCTCCCT motif was found to be overrepresented at hotspots in the THE1A/B retrotransposon which is primate specific (Smit 1993;Myers et al 2005Myers et al , 2008Pace and Feschotte 2007). Furthermore, Myers et al (2008) suggested that any generic hotspot-promoting motif should operate on diverse genetic backgrounds (such as in different repeat families) in human, and revealed the presence of a common 13-bp degenerated motif (CCNCCNTNNCCNC) that is recognized by the DNA-binding and chromatin-modifier PRDM9 protein (Baudat et al 2010).…”
mentioning
confidence: 99%
“…Initially in human, the CCTCCCT motif was found to be overrepresented at hotspots in the THE1A/B retrotransposon which is primate specific (Smit 1993;Myers et al 2005Myers et al , 2008Pace and Feschotte 2007). Furthermore, Myers et al (2008) suggested that any generic hotspot-promoting motif should operate on diverse genetic backgrounds (such as in different repeat families) in human, and revealed the presence of a common 13-bp degenerated motif (CCNCCNTNNCCNC) that is recognized by the DNA-binding and chromatin-modifier PRDM9 protein (Baudat et al 2010).…”
mentioning
confidence: 99%
“…This scenario would also imply that some ancestral SPIN copies have been retained at orthologous genomic positions in some of these species or in the sister taxa represented in the databases. Such ancient transposon fossils are generally well preserved in the genomes of eutherians owing to their relatively slow substitution rates (26)(27)(28). However, with the exception of mouse and rat, where nearly all SPIN elements were found at orthologous genomic positions and therefore must have inserted before the divergence of these rodents (Fig.…”
mentioning
confidence: 99%
“…To gain further insight into the timing of the transfers, we derived an estimate of the time elapsed since the amplification of SPIN families in each of the host species lineages. Because the elements have evolved neutrally since their insertion, the age of individual insertions can be approximated by measuring the sequence divergence from the ancestral consensus sequence and by applying a neutral substitution rate characteristic of the species lineage (26)(27)(28). To estimate the neutral substitution rate in the lineages of bushbaby, murine rodents, bat, and tenrec, we retrieved, aligned, and compared a large and diverse set of ancient transposable elements present at orthologous genomic positions in human, which is known to have diverged from each of these species Ϸ80, 89, 94, and 104 mya, respectively (see SI Materials and Methods).…”
mentioning
confidence: 99%
“…Most of them have occurred after divergence from the last common ancestor (Mills et al 2006) and retrotransposition continues to contribute to human genetic diversity (Seleme et al 2006). Even DNA transposons, which are not capable of active transposition in the human genome, were intensively active during early primate evolution (Pace & Feschotte 2007). In fish, many bursts of retrotransposition potentially associated with speciation events have been observed for non-LTR retrotransposons (Volff et al 2000(Volff et al , 2001c.…”
Section: Transposable Elements and Biodiversity In Vertebratesmentioning
confidence: 99%